A case–control study on vitamin D receptor gene polymorphisms in patients with Parkinson’s disease in Bangladesh - Narayan Chandra Kundu; Anindya Kundu; Md. Ibrahim Khalil; K. M. Nazmul Islam Joy; Moushumi Sen; Zahid Hasan; Md. Sahabuddin; Md. Abdur Rafi; Mohammad Jahid Hasan (Scientific Reports)
Abstract Parkinson’s disease (PD) is a neurodegenerative disorder with a multifactorial etiology. This study aimed to investigate the association between vitamin D receptor (VDR) gene polymorphisms (ApaI, BsmI, FokI and TaqI) and the risk of PD in a Bangladeshi population. A case-control study was conducted with 100 PD patients and 100 age- and sex-matched healthy controls. Serum vitamin D levels were measured using a chemiluminescent immunoassay, and VDR gene polymorphisms were genotyped using the polymerase chain reaction-restriction fragment length polymorphism (PCR-RFLP) technique. Genetic models (allele, dominant, recessive and additive models) were used to assess the association between each polymorphism and PD risk. The mean age of the patients with PD was 63 years, with 65% being male, while the control group had a mean age of 54.5 years and 60% were male. In genetic models, the T allele of the ApaI gene demonstrated a significant association with PD (OR 1.92, 95% CI 1.20–3.13, p-value 0.007). This significant association persisted across both recessive and additive models (for recessive model: OR 2.17, 95% CI 1.10–4.55, p-value 0.027 and for additive model: OR 2.78, 95% CI 1.22–6.67, p-value 0.015). Similarly, the T allele of the FokI gene was found to be significantly associated with PD (OR 2.27, 95% CI 1.43–3.57, p-value 0.001). This association was also evident in both dominant and additive models (for dominant model: OR 2.56, 95% CI 1.45–4.55, p-value 0.001 and for additive model: OR 3.03, 95% CI 1.67–5.56, p-value 0.001). Conversely, no significant associations were observed for the genetic polymorphisms of the BsmI and TaqI genes across any of the genetic models examined. The findings suggest that specific VDR gene polymorphisms, particularly ApaI and FokI, are significantly associated with the risk of PD in the Bangladeshi population.